Social Construction of Health in the Educational Sphere: A Literature Review - Dina Arianti; Subhan, Dwiyani; Moh Arib Ramdhana; Ibrahim Arifin (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
This study is rooted in the growing recognition that health within educational settings is not merely a physical condition but a socially constructed reality shaped through institutional interactions, cultural norms, and school policies. The aim of this research is to examine how meanings of health are constructed, reproduced, and interpreted by members of the school community. A qualitative descriptive approach with a narrative literature review design was employed to collect, synthesize, and critically analyze scholarly publications from the last decade related to school health, student wellbeing, and health literacy. Thematic analysis was used to identify central patterns and conceptual themes across the literature. Findings indicate that school climate, social relationships, family involvement, and pedagogical practices play essential roles in shaping students’ understanding of health, while structural barriers such as limited resources, unequal service provision, and weak program coordination—hinder the development of comprehensive health cultures in schools. The study concludes that health in education is a socially negotiated construct requiring holistic, collaborative, and sustained approaches. These insights contribute theoretically to social construction literature and offer practical recommendations for strengthening school health policy and practice.